Assessment of ecological stress caused by maritime vessels based on a comprehensive model using AIS data: Case study of the Bohai Sea, China - Baijing Liu (Elsevier, 2021)
Increased maritime vessel activity has adversely affected the conservation of marine environments. The mobility and diverse operations of vessels increase the difficulty of marine spatial planning and protected-area management. This study proposed a “source-pathway-carrier-impact-response” (SPCIR) model to describe marine ecological stress caused by vessels (VES) and constructed a comprehensive assessment index system. The method was applied to the Bohai Sea in China using automatic identification system (AIS) data and geographic information system (GIS) spatial analysis. The results showed an obvious increase in VES from 2014 to 2018, with noise pollution, light pollution, and hydrodynamic interaction being the most prominent. Cargo vessels and oil tankers were the main stressors. Vessel activity seriously affected agriculture and fishery functions as well as marine-reserved zones in the Bohai Sea. The proposed SPCIR model can effectively identify the level and spatiotemporal characteristics of various vessel-related impacts and efficiently determine management priorities. It can provide a theoretical basis for marine area management and be conveniently adopted by management departments in various regions.